Executive Presence - Trey Guinn (Academic Chairpersons Conference Proceedings, 2019)
Strengthening executive presence and communication skills enhances effectiveness as chairperson and beyond. To inspire change and achieve results, chairpersons must create and deliver persuasive messages with impact. Following an interactive workshop loaded with laughter, group activity, role-play, and various simulations, participants will leave with fresh perspective on how to be a more clear, concise, compelling, and confident communicator capable of exuding greater executive presence.
Keywords: executive presence; leadership; communication skills; persuasion; impact